(untitled) (Journal of School Administration Research and Development, 2024)
This study sought to identify how first-grade students in one Midwest state cognized hope. Using a case-study research method, the authors identify recommendations for practice that draw on the alignment between developing hope in students through school leadership. Previous research has highlighted school leadership’s significant role in multiple pathways for student success. This study demonstrates that young children can cognize abstract topics such as hope and presents ways educational leaders can support student social-emotional well-being in the daily curriculum through hope education.